2003
DOI: 10.1001/archsurg.138.3.286
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intraperitoneal Antiadhesive Fluids in a Rat Peritonitis Model

Abstract: Phospholipids and icodextrin reduce peritoneal adhesions resulting from general peritonitis without promoting abscess formation. Design: Evaluation of adhesion reduction fluids in a randomized animal study using a standardized peritonitis model. Setting: Experimental animal model in a university laboratory. Interventions: In 60 rats, experimental peritonitis was induced using the cecal ligation and puncture model. On day 1, the abdominal cavity was rinsed with 10 mL of isotonic sodium chloride solution and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 33 publications
1
19
0
4
Order By: Relevance
“…[23] Peritonitis seems to be the major cause of intraabdominal adhesion formation, but there are not enough experimental and clinical studies on this issue. [24] Generalized infection in the abdominal cavity affects abdominal tissues in relation to operative materials and fluids. While results of some materials tested in the prevention of adhesion formation were reported in a limited number of studies in the literature, an ideal material has yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[23] Peritonitis seems to be the major cause of intraabdominal adhesion formation, but there are not enough experimental and clinical studies on this issue. [24] Generalized infection in the abdominal cavity affects abdominal tissues in relation to operative materials and fluids. While results of some materials tested in the prevention of adhesion formation were reported in a limited number of studies in the literature, an ideal material has yet to be identified.…”
Section: Discussionmentioning
confidence: 99%
“…[9,10] To avoid adhesion formation in peritonitis, tenoxicam, aminoguanidine, beta glucan, polysaccharide carboxy methyl cellulose and phlennium saprophyte have been used in different studies. [11][12][13][14] Adhesion formation is associated with significant oxidative stress, both from the activation of the mesothelium and underlying endothelial cells and, more importantly, from the infiltration and subsequent activation of neutrophils and macrophages and cytokines. [15][16][17] Methylene blue (MB) acts as an antioxidant and may reduce intraabdominal nascent fibrinous adhesions, and is rapidly degraded via intraabdominal proteases such as tissue plasminogen activator (tPA), which is a major component of the peritoneal fibrinolytic system.…”
Section: Methodsmentioning
confidence: 99%
“…In their experimental study performed to prevent epidural fibrosis, Kemaloglu et al (20) reported that topical recombinant tissue plasminogen activator (rt-PA) was effective and reliable, and that a thrombolytic therapy including rt-PA might play an important role in preventing arachnoiditis and epidural fibrosis following spinal surgery. In an experimental peritonitis model, it has been suggested that 4% icodextrin solution prevents epidural fibrosis by profibrinolytic stimulation after stimulating rt-PA synthesis (24). In the present experimental laminectomy model which was planned based on this hypothesis, histopathological (macroscopic and microscopic) and biochemical outcomes revealed that 4% icodextrin solution prevented postoperative epidural fibrosis likely due to profibrinolytic stimulation.…”
Section: █ Conclusionmentioning
confidence: 60%
“…Его 7,5% рас-твор применяется с целью перитонеального диализа у 4000 больных в год. Известный как препарат Adept, 4% раствор икодекстрина широко применяется как противоспаечное средство в общей хирургии и ги-некологии и, по данным ряда авторов, способен уменьшить спайки на 32-52% [6][7][8].…”
unclassified
“…В клинических работах с целью профилактики спаечной болезни еще не при-менялись фосфолипиды, однако в эксперименталь-ных работах применение фосфатидилхолина приве-ло к хорошим результатам как при перитоните, так и без него, без отрицательного влияния на заживле-ние раны или анастомозов [7].…”
unclassified